Answer:
x=78
Step-by-step explanation:
q is 90 degrees since it is a right angle,
p=12
90 plus 12 =102
x=180-102
x=78
This is what I got pls mark me brainlest
Answer:
-3<x<3
Step-by-step explanation:
let y=0
0=x^2-9
0=(x+3)(x-3)
x=-3 and x=+3
The average rate of change is 1
2-1=1
3-2=1
4-3=1
answer
(x+7)^2 + (y-4)^2 = 64
set up equation
the equation of a circle is (x - h)^2 + (y - k)^2 = r^2
where h is the center x coordinate and k is the center y coordinate
values
from the point (-7,4) we know that h = -7 and k = 4
since the radius is 8, r^2 = 8^2 = 64
plug in values
now that we have all the values, we plug them into (x - h)^2 + (y - k)^2 = r^2
(x - h)^2 + (y - k)^2 = r^2
(x - (-7))^2 + (y-4)^2 = 64
(x+7)^2 + (y-4)^2 = 64